(untitled) (Academicia Globe: Inderscience Research, 2022)
Lead is a toxic material that may damage the environment and leads to major health issues, especially in children, due to its cumulative toxic nature and adverse effects on several bodily systems. High concentrations of the element of lead were found in certain soil samples, which had health implications on children by determining the level of lead in the students’ blood samples in those schools. It was observed that there is a correlation between high concentrations of lead in soil samples taken from indoor gardens in schools and the high amount of lead in the blood samples of the students at those schools. Lead concentrations were measured by using a flame Atomic Absorption Spectrophotometer.